Fishing Crafts and Gears Used Along Selected Stretch of River Mahanadi - Sudheesan, Deepa; Sajina A. M.; S. Samanta; S. K. Paul; S. K. Nag; Raju Baitha; S. Bhowmick (Fishery Technology, 2023)
Mahanadi is one of the major peninsular rivers of India which harbours rich ichthyofaunal diversity. The fisher folk employ various fishing methods to harvest fish for their livelihood and nutritional requirements. Information on fishing crafts and gears was collected from 11 stations from Seorinarayan (Chhattisgarh) to Paradeep (Odisha) along the river Mahanadi from December 2012 to February 2015. The most dominant type of craft is the plank-built boat of varying sizes, locally called ‘donga’. Various types of gears were recorded along the river stretch among which gill nets are the most widely used. Polyamide monofilament and multifilament gill nets of 20-120 mm mesh size are popular. Cast nets are the next dominant fishing gear, operated from both the river bank and boat. Trap fishery, locally called ‘benda’/’baja’, is mainly used in the rocky areas of river stretch. Bag nets and seine nets were also employed towards the lower stretch of the river. Indigenous fishing gears specific for species and locale, made from locally available materials were also recorded. ‘Khadi jal’ is a type of drag net with a long wall of netting supported vertically by bamboo sticks. Sola-kontai fishing uses a hook and line in which multiple hooks are hidden inside baits made of dough containing rice flour, mud and plant extract as chemo-attractant and the depth of operation is maintained by plant fibre floats. ‘Chhinajaal’ is a type of hand lift net, operated usually by women and children. A type of barrier net fishing was observed at open barrage shutters where nets are fixed to catch fish jumping against the flow. Dynamite fishing, a destructive fishing practice is rampant in Mahanadi, particularly in Sonepur which has severe impacts on the ichthyofauna of the river. Though gillnets are extensively used, diverse traditional fishing gears continue to prevail along Mahanadi. Documentation of these gears and their mode of operation holds significance as it throws light on the traditional fishing knowledge of the community and provides an understanding of their cultural heritage.